Application of the Problem Based Learning Model with Pancasila Behavior Pocket Media to Improve Student Learning Outcomes - Yasa, Arnelia Dwi; Alvinarista, Anida; Muzakir, Fathol (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2025)
This research is motivated by the low student learning outcomes observed during preliminary activities in the classroom. Several factors contribute to this issue, including the use of less effective learning models and media, which result in limited student participation and overall low achievement. The purpose of this study is to improve student learning outcomes in Pancasila Education for grade III students by applying the Problem Based Learning (PBL) model supported by Pancasila Behavior Pocket media. This study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings and involving four stages: planning, implementation, observation, and reflection. Data collection techniques included observation, documentation, and learning outcome tests. The research findings in Cycle I showed that students' mastery of the material increased from 57% in the pre-test to 71% in the post-test. In Cycle II, the pre-test score rose to 71%, and the post-test score reached 81%. This steady improvement indicates that the implementation of the PBL model combined with contextual media can effectively enhance student learning outcomes. The integration of the Pancasila Behavior Pocket media provided engaging, relevant, and practical learning experiences, increasing student participation and understanding. These findings suggest that Problem Based Learning supported by appropriate media can serve as an effective strategy to improve learning outcomes in Pancasila Education at the elementary school level.